THE RISK OF BEING UNSYSTEMATIC AND STOCK RETURNS: THE EMPIRICAL TEST ON CAPITAL VALIDITY OF CAPITAL ASSET PRICING MODEL - Arfiana Rachel (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2014)
The objective of this research is to analyze the effect of idiosyncratic risk to stock return on Indonesia Stock Exchange. To test these variables, the study applied two pass regression with time series data of stock return LQ45 and stock price index from January 2014 - December 2014. The estimation method used in the first pass regression was selected by characteristics of the return data, that is EGARCH (1,1) method for heterokedasticity data and Ordinary Least Squares for constant variance data. Specifications on the second pass regression models using cross section data, that is month by month cross sectional regression of 30 stock portfolios, which aim to identify unsystematic risk role in explaining the behavior of the return from stock portfolio. The findings of this study indicate that unsystematic risk has insignificant effect on stock return. These findings support the statement postulated in Capital Asset Pricing Model (CAPM), that the only relevant risk in explaining the return of stock only systematic risk, so there is no statistical evidence is strong enough to declare that the unsystematic risk can play a role in explaining the movement of stock return.